Hubungan Pola Makan dan Aktivitas Fisik dengan Kejadian Hipertensi pada Dewasa: The Relationship Between Dietary Patterns, Physical Activity, and the Incidence of Hypertension in Adults - Tommy Wowor; Andi Mayasari Usman; Mia Atlantic; Shifa Hera Saputri (MPI Press, 2026)
Introduction: Hypertension remains a major global health problem with a continuously increasing prevalence. In 2024, approximately 1.4 billion people worldwide were estimated to have hypertension. In Indonesia, around 51.3 million individuals aged 30-79 years suffer from hypertension, while in DKI Jakarta there were 923,451 reported cases. Unhealthy dietary habits and insufficient physical activity are among the primary risk factors contributing to the development of hypertension, particularly among adults.Objectives: To determine the relationship between dietary patterns and physical activity with the incidence of hypertension among adult patients at Karet Kuningan Community Health Center.Method: This study employed a quantitative research design with a cross-sectional approach. A total of 73 adult respondents were selected using purposive sampling. Data were collected using the Food Frequency Questionnaire (FFQ) to assess dietary patterns, the Global Physical Activity Questionnaire (GPAQ) to measure physical activity levels, and blood pressure measurements using a digital sphygmomanometer. Data were analyzed using univariate and bivariate analyses with the Chi-Square test.Result: The findings revealed that 65.8% of respondents had unhealthy dietary patterns and 47.9% had low levels of physical activity. The prevalence of hypertension among respondents was 69.9%. Statistical analysis showed a significant relationship between dietary patterns and hypertension incidence (p = 0.001; OR = 246.750). In addition, a significant relationship was found between physical activity and hypertension incidence (p = 0.001).Conclusion: There is a significant relationship between dietary patterns and physical activity with the incidence of hypertension among adult patients at Karet Kuningan Community Health Center. Improving public awareness through nutrition education and the promotion of regular physical activity is essential to support healthy lifestyles and prevent hypertension.